The influence of service value and customer retention on the green marketing mix model for local Indonesian clothing brands - Aswan, Muhammad Kholil; Setyaningrum N , Krisnawati; Intiar, Septa (Jurnal Mantik, 2024)
This research aims to see the influence of the Green Marketing Mix on Customer Retention. Seeing the influence of the Green Marketing Mix on Service Value. Seeing the influence of Service Value on Customer Retention. As well as seeing the influence of the Green marketing mix on customer retention through service value in local Indonesian clothing brands. This research uses the AMOS SEM analysis technique to see the influence of exogenous variables on endogenous variables. 200 respondents and analyzed research instruments for validity and reliability and tested hypotheses and sobel tests. From the research results, it was found that there is an influence of the Green Marketing Mix on Customer Retention. There is an influence of the Green Marketing Mix on Service Value, there is no influence of Service Value on Customer Retention. There is no influence of the Green marketing mix on customer retention through service value in local Indonesian clothing brands